Transferosomes - A vesicular transdermal delivery system for enhanced drug permeation - Reshmy Rajan; Shoma Jose; V P Biju Mukund; Deepa T Vasudevan (Wolters Kluwer Medknow Publications, 2011)
Transdermal administration of drugs is generally limited by the barrier function of the skin. Vesicular systems are one of the most controversial methods for transdermal delivery of active substances. The interest in designing transdermal delivery systems was relaunched after the discovery of elastic vesicles like transferosomes, ethosomes, cubosomes, phytosomes, etc. This paper presents the composition, mechanisms of penetration, manufacturing and characterization methods of transferosomes as transdermal delivery systems of active substances. For a drug to be absorbed and distributed into organs and tissues and eliminated from the body, it must pass through one or more biological membranes/barriers at various locations. Such a movement of drug across the membrane is called as drug transport. For the drugs to be delivered to the body, they should cross the membranous barrier. The concept of these delivery systems was designed in an attempt to concentrate the drug in the tissues of interest, while reducing the amount of drug in the remaining tissues. Hence, surrounding tissues are not affected by the drug. In addition, loss of drug does not happen due to localization of drug, leading to get maximum efficacy of the medication. Therefore, the phospholipid based carrier systems are of considerable interest in this era.